TRADISI KAWIN NGARAH GAWE DALAM PANDANGAN HUKUM ISLAM (Studi di Desa Bukit Harapan Air Rami Kabupaten Mukomuko) - Sultanudin, Atep; Fahimah, Iim; Taman, Badrun (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2022)
This paper discusses the implementation of the Ngarah gawe marriage tradition in Bukit Harapan Village, Air Rami District, Mukomuko Regency, Bengkulu province, and how it is reviewed from the perspective of Islamic law. The research method used in this research is using the field research method (field research). The location of the research is in Buki Harapan Village, Air Rami District, Mukomuko Regency, and the data collection techniques are interview, observation and documentation methods. The results of the research are: (1) the implementation of the ngarah gawe marriage tradition is as follows; narosan, seserahan, ngaras, ngeuyeuk seureuh, and marriage contracts, with the aim of preparing to create a harmonious, peaceful and peaceful family through the assessment of the in-laws. (2) as for the process of implementing the ngarah gawe tradition, it does not conflict with Islamic Shari'a because in the process of implementation, the values or Islamic Shari'a are not forgotten in the slightest.